(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Inflation targeting has been extensively embraced in both advanced and developing nations. This article examines the evidence on the impact of inflation targeting on macroeconomic performance and evaluates the implications of this data for inflation targeting and monetary policy design. Although there have been similarities in macroeconomic experiences between inflation targeting and non-targeting established nations, it is evident that inflation targeting has enhanced macroeconomic performance in emerging economies. Crucially, the practice of inflation targeting has not been linked to increased actual economic instability in either advanced or emerging economies. Cost shocks, such as the significant increase in commodity prices, need central banks to make challenging immediate decisions. However, a commitment to a specific aim might improve the capacity to handle demand shocks and financial crises. This study analyzes the progression of monetary policy goals and how, after a deviation, it has reverted back to focusing on controlling inflation, similar to the approach during the Gold Standard (GS) era.